Efficacy of a four-week uphill sprint training intervention in field hockey players - Jakeman, J. R.; McMullan, J.; Babraj, J. A. (The Journal of Strength and Conditioning Research, 2016)
Current evidence increasingly suggests that very short, supramaximal bouts of exercise can have significant health and performance benefits. Most research conducted in the area, however, uses laboratory-based protocols, which can lack ecological validity. The purpose of this study was to examine the effects of a high-intensity sprint training program on hockey-related performance measures. Fourteen semiprofessional hockey players either completed a 4-week high-intensity training (HIT) intervention, consisting of a total of 6 sessions of HIT, which progressively increased in volume (n = 7), or followed their normal training program (Con; n = 7). Straight-line sprint speed, with and without a hockey stick and ball, and slalom sprint speed, with and without a hockey stick and ball, were used as performance indicators. Maximal sprint speed over 22.9 m was also assessed. On completion of the 4-week intervention, straight-line sprint speed improved significantly in the HIT group (~3%), with no changes in performance for the Con group. Slalom sprint speed, both with and without a hockey ball, was not significantly different after the training program in either group. Maximal sprint speed improved significantly (12.1%) in the HIT group, but there was no significant performance change in the Con group. The findings of this study indicate that a short period of HIT can significantly improve hockey-related performance measures and could be beneficial to athletes and coaches in field settings.